2019
DOI: 10.3390/drones3020031
|View full text |Cite
|
Sign up to set email alerts
|

A K Nearest Neighborhood-Based Wind Estimation for Rotary-Wing VTOL UAVs

Abstract: Wind speed estimation for rotary-wing vertical take-off and landing (VTOL) UAVs is challenging due to the low accuracy of airspeed sensors, which can be severely affected by the rotor’s down-wash effect. Unlike traditional aerodynamic modeling solutions, in this paper, we present a K Nearest Neighborhood learning-based method which does not require the details of the aerodynamic information. The proposed method includes two stages: an off-line training stage and an on-line wind estimation stage. Only flight da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Ultimately, while our methods build upon existing theoretical frameworks proposed by [ 9 , 10 ], to the best of our knowledge this work presents the first scientific investigation of a real-world application using machine learning methods to accurately predict windspeeds using onboard drone attitude and inertial data. During placid periods of wind activity, we found that the linear model performed on par with the KNN algorithm and LSTM neural network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, while our methods build upon existing theoretical frameworks proposed by [ 9 , 10 ], to the best of our knowledge this work presents the first scientific investigation of a real-world application using machine learning methods to accurately predict windspeeds using onboard drone attitude and inertial data. During placid periods of wind activity, we found that the linear model performed on par with the KNN algorithm and LSTM neural network.…”
Section: Discussionmentioning
confidence: 99%
“…Such methods, while shown to be effective, are less extendable to other drone models than our proposed methodology, which eliminates the need for complex mathematical representations by instead learning the wind-attitude relationship directly from available attitude data. Work in [ 9 ] established the feasibility of using k-nearest neighbors (KNN) for rotary-wing-based windspeed estimation. However, speeds in their indoor experimentation did not exceed 3.07 m·s −1 , which constrains the applicability and representativeness of their findings.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the ideal hover is possible when = 0 and all forces which act on a quadcopter are compensated. The roll, pitch, and yaw angles in a turbulent atmosphere are sums of the average and fluctuation components: (19) can be transformed to the case of ideal hover by means of their linearization. In the small-angle approximation , ≪ π, at ′ ≪ and under the conditions ̈=̈=̈= 0 and = 0, the equations for estimates of the horizontal components of the wind field � = and � = take the forms…”
Section: Estimates Of the Wind Velocity Componentsmentioning
confidence: 99%
“…The K Nearest Neighborhood learning-based method is suggested in [19] for rotary-wing vertical take-off and landing UAVs. Experimental results obtained with the use of a Parrot AR.Drone demonstrate the accuracy and robustness of the developed wind estimation algorithms under hovering conditions.…”
Section: Introductionmentioning
confidence: 99%
“…to heights of about 500 m, is the development of methods for diagnostics of the turbulent atmosphere with UAVs. The results of diagnostics of the speed of air mass flows with UAV are reported in [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In [36][37][38][39][40][41][42][43][44][45][46], the fundamental possibility of measuring the turbulence spectra with fixed-wing UAVs of various sizes and weights was shown.…”
Section: Introductionmentioning
confidence: 99%